Using Interest Management to Improve Load Balancing in Distributed Simulations - Bacelar, Felipe C.; Lucena, Carlos J. P. de; Bommel, Pierre (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC); 2013: Anais do VII Workshop-Escola de Sistemas de Agentes, seus Ambientes e AplicaçõesDO - 10.5753/wesaac.2013.33192, 2013)
This paper presents an approach to distribute an agent-based simulation over a network of computers. The developed work aims at improving the load balancing of the simulation distribution. In order to reach such objective, we propose to use an Interest Management technique presented by Brian Logan and Georgios Theodoropoulos who proposed to distribute a simulation by dynamically partitioning the environment according to the Interest of the agents. In order to assess its efficiency, we have re-implemented this model using the distribution mechanisms provided by some of the main multiagent system platforms.